Psychometric Properties of the Proactive Personality Scale in schoolteachers in Lima (Peru) - Bojorquez-Paucar, Josselyn María (2022)
The objective was to evaluate the psychometric properties of the Proactive Personality Scale in a sample of teachers from schools in Lima (Peru). Participants were 302 teachers of both sexes (72.20% women) selected through a non-probabilistic sampling of intentional type, whose ages were in the range from 24 to 65 (M = 43.04, DE = 10.75) and who taught at the educational levels of primary and secondary education (75.83% in secondary education). In addition to the Proactive Personality Scale, the Teachers Self Efficacy Scale was applied to assess convergent validity. The results indicate that the Proactive Personality Scale was adjusted to a unifactorial structure (CFI = .949, TLI = .934, RMSEA = .076 y SRMR = .044), there are statistically significant correlations (p <.001) and with a mean effect size (rs> .10) with most of the dimensions of self-efficacy feeling and adequate internal consistency (.89). The Proactive Personality Scale has evidence of validity based on internal structure, convergent validity, and adequate reliability to measure proactive personality in schoolteachers.